Implementing Problem-Solving Activities to Enhance Critical Thinking Among EFL Young Learners (2021)
ABSTRACT:This action research aimed to identify to what extent the implementation of problem- solving activities enhances EFL young learners’ critical thinking. The participants were 15 students from PINJ (Programa de Inglés para Niños y Jóvenes) from Universidad de Antioquia. Actions consisted in the creation of problem-solving activities around subtopics related to students' realities and context: gender role issues and gender inequality within the families; elder mistreatment and abandonment; and violence on Mother’s Day. The activities were developed introducing the issue, its causes and consequences, encouraging students to propose solutions from their point of view. Data collection instruments included a teacher journal, a student survey, and an interview with my CT. Findings suggest that problem-solving activities fostered students’ critical thinking, participation, motivation, and language skills.